SPARSE CYLINDRICAL AND CONICAL ANTENNA ARRAYS - O. A. Yurtsev; S. A. Zavadski (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Cylindrical and conical antenna arrays numerical simulation results are presented. Radiation pattern and directivity coefficient dependence from array sparseness factor is observed.